Employee Workload Analysis at The Financial Services Authority Human Resources Management Directorate with Full Time Equivalent (FTE) - Prasetyo, Gedeon Budi; Sukamdani, Nugroho BS.; Sukwika, Tatan (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The Financial Services Authority (OJK) is a public institution that has a statutory mandate to regulate and oversee the financial services sector and protect consumers. At the present time, the financial services sector is experiencing positive developments so that the OJK is also supporting this function by providing human resources. So that there is an increase in staff at OJK resulting in an increase in workload at the Directorate of Human Resources Management (DLSM) which has the function of managing human resources. On the other hand, OJK has not yet calculated employee workload and does not yet have a standardized method for calculating employee workload and employee needs. This study aims to analyze the current workload of employees with Full Time Equivalent (FTE) and the ideal employee needs as well as provide strategies to deal with underload, normal, and overloaded workload scale conditions in the Directorate of Human Resource Management at the Financial Services Authority. The results of the research that has been done are 12 employees in the Overload workload category, 13 employees in the Normal workload category, and 1 employee in the Underload workload category. Based on this FTE calculation, it is known that there is a shortage of 23 people. So several steps are proposed to meet the needs of employees and to equalize the workload of employees in the DLSM. The results of the research that has been done are 12 employees in the Overload workload category, 13 employees in the Normal workload category, and 1 employee in the Underload workload category. Based on this FTE calculation, it is known that there is a shortage of 23 people. So several steps are proposed to meet the needs of employees and to equalize the workload of employees in the DLSM.